High step‐up quasi‐Z‐source converter with full soft switching range, continuous input current and low auxiliary elements - Maryam Hajilou; Mohsen Packnezhad; Hosein Farzanehfard (IET Power Electronics, 2023)
Abstract This paper presents a fully soft switched high step‐up DC–DC converter based on quasi‐Z‐source converter. The voltage gain is boosted by combining coupled inductors and switched capacitor techniques. Moreover, a ZVT cell comprising of only a single switch and an inductor coupled to the quasi‐Z‐source inductor is utilized to reduce the magnetic cores and realize soft switching for all semiconductors without imposing any extra voltage or current stress on the converter elements. The main switch operates at zero voltage switching and zero current switching (ZCS) at turn‐on which is independent of the load and duty cycle variations. Hence, soft switching condition for the main switch at turn‐off is easily provided by a snubber capacitor. In addition, the reverse recovery problem of all the converter diodes is significantly mitigated by ZCS at turn‐off while the continuous current at the input source is maintained. In order to verify the theoretical analysis and the proposed converter operation, a converter prototype is implemented at 300 W and 100 kHz. Finally, a comprehensive comparison is performed between the proposed converter and other high step‐up converters based on quasi‐Z‐source structure, to demonstrate the merits of the proposed converter.